THE ELEMENTAL COMPOSITION OF GARDEN SWAN (ATRIPLEX HORTENSIS L.) GROWING IN GORIS (SYUNIK REGION, ARMENIA) - Vardanyan, L.; Hayrapetyan, S. (SUSh Scientific Proceedings, 2025)
The article presents the results of a study on the elemental composition of the aerial parts of Garden Orach (Atriplex hortensis L.) growing in the outskirts of Goris, a city in Syunik Region of Armenia. Using inductively coupled plasma optical emission spectroscopy (ICP-OES), the contents of 33 elements were determined in both plant material and soils. It was established that garden orache exhibits a high level of essential elements: potassium (43947.60 mg/kg), calcium (19212.68 mg/kg), magnesium (5908.99 mg/kg), phosphorus (5030.41 mg/kg), and sulfur (3439.98 mg/kg). Among the microelements, iron (207.13 mg/kg), aluminum (175.55 mg/kg), zinc (59.72 mg/kg), and manganese (50.49 mg/kg) are the most prevalent. The biological absorption coefficients (BAC) of these elements were calculated, revealing a selective accumulation of potassium (BAC = 9.26), sulfur (BAC = 6.27), and phosphorus (BAC = 1.45) by the plant. Most microelements are characterized by low BAC values (< 1), indicating the presence of barrier mechanisms in garden orache that limit their entry into the aboveground organs. A low content or complete absence of potentially toxic elements (Pb, Sb, W) in the plant material was noted. The results obtained indicate the value of garden orache as a source of essential macro- and microelements in the human diet and confirm the ecological safety of plant raw materials from the studied region